تأويل الخطاب القرآني في الفكر العربي المعاصر مقاربة بين نصر حامد أبو زيد والقاضي عبد الجبار الهمذاني - رحال, هشام (جامعة الوادي - University of Eloued, 2021)
إنّ النّص القرآني موضوع التّأويل ليس منغلقا انغلاقا تامًّا بحيث لا يلج عوالمه إلا القلّة من القرّاء، كما أنّه ليس منفتحا انفتاحا كلّيًا بحيث يقبل أيّ تأويل يوضع له، ثم إنّ المتطلّع على الخطابات التفسيرية المتعدّدة يجد أنّها منفتحة على مجالات عديدة فقهية ولغوية، وبلاغية، وأدبية، ومنطقية، وهذا ما جعلها مجالا لانتظام حقول معرفية متباينة لكنها متعاونة في فهم المعنى، وتبعا لذلك يجد قرّاء ومحلّلو هذا الخطاب تقاطعات عمودية وأفقية بين مواد النّصوص القرآنية موضوع التّأويل لدى المؤوّل.والمنقّب في التّراث العربي يحصل على قراءات تأويلية منتظمة متينة مبنية على منطق تساند الآليات وتعاون المستويات البنائية بنظيرتها الخارجية، وهو أمر تحقّق في الخطاب التّأويلي لدى القاضي عبد الجبار الهمذاني. وعلى ضوء هذا تتحقق العملية التّأويلية لدى للقارئ الذي يكون قد تزوّد باستراتيجية قرائية وبذخيرة من النّصوص تسمح له باكتشاف العلاقات الدلالية، بالإضافة إلى كفايته الافتراضية والتصوّرية والموسوعية التي تمكّنه من إشباع الدّلالة، وهو أمر قدّم له نصر حامد أبو زيد، لذلك فإنّ تصوّرنا للموضوع ينبني على ضرورة التعرّف على العناصر التّأويلية البليغة ذات المعايير والإجراءات المحدّدة التي استطاع كل من القاضي وأبو زيد تبرير مفاهيمهما وتخريجاتهما. الدّافع إلى الولوج إلى هذا النّوع من الطّرح هو تنوير إشكالية تتّسم بفضاء معرفي شاسع مفاده: ماهية التّأويل؟ وماهي الآليات العاملة في هذا الفضاء؟ هل انماز كل منهما بإجراءات منفردة عن الآخر؟. فالواقع المعرفي والوجودي المبني على التّفكير والتدبّر وإعطاء الأشياء مقاديرها التي تستحقها هو الدافع والله من وراءه القصد والنية. الكلمات المفتاحية:التأويل، القرآن، مقاربة، الفكر، الخطاب. Abstract: The Qur’anic text, the subject of exegesis, is not completely inaccessible, so that only a few of the readers infiltrate into its worlds, and it is not fully open to accept any interpretation that is attributed to it. Moreover, those looking at the various interpretive discourses find that they are open to many areas of jurisprudence, linguistic, rhetorical, literary, and logical nature, and this is what made them a field for the regularity of different fields of knowledge but cooperative in understanding the meaning, and accordingly readers and analysts of this discourse find vertical and horizontal intersections between the quranic texts; the subject of exegesis for the interpreter. The examiner of Arabic heritage gets regular and solid interpretive readings based on the logic of cooperative mechanismsand the support of structural levels with their external counterparts. This is something that was achieved in the interpretive discourse of Al-Qadi Abdul-Jabbar Al-Hamdhani. In light of this, the interpretive rhetoric is realized for the reader, who was providedwith a reading strategy and panoply of texts that allow him to discover semantic relations, in addition to his hypothetical, visual and encyclopedic sufficiency that enable him to satisfy the connotation, something that was achieved by Nasr Hamid Abu Zayd. So, our perception of the subject is based on the necessity of identifying the eloquent interpretive elements with specific standards and procedures that both Al-Qadi and Abu Zayd were able to justify their concepts and paradigms. Perhaps the motivation for accessing this type of discourse is to enlighten an issue characterizedby a vast knowledge space that is: What is the rhetoric of interpretation? What are the mechanisms operating in this space? Did each of them have separate proceduresdifferent than the other’s? The cognitive and existential reality based on thinking and contemplation and giving things their worthy amounts is the motive and God is behind our intention. Key words: Interpretation - Qur’an - Approach - Thought - Discourse.
مقال
Keywords: التأويل، القرآن، مقاربة، الفكر، الخطاب